Philosophical profiles in the theory of communication [ - Hannan, Jason , 1976- (Peter Lang, 2012)
Covers a range of philosophical perspectives on communication, including those from analytic philosophy, pragmatism, critical theory, psychoanalysis, systems theory, and more. This book draws attention to the theme of communication in twentieth-century academic philosophy. It is suitable for courses in philosophy and communication studies